Effect of rice bran protein concentrate as wall material adjunct on selected physicochemical and release properties of microencapsulated β-carotene - Magnaye, Maria Jannell Feliz A (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2022)
Rice bran protein is an emerging protein source from rice milling that possesses health benefits and emulsifying capacity suitable for hypoallergenic encapsulation applications, especially for lipophilic compounds such as β-carotene. The purpose of this study is to develop and characterize β-carotene encapsulates with maltodextrin and rice bran protein. Rice bran protein was prepared using conventional alkali extraction. β-carotene was added to the composite wall materials (50:50 of 4%, 8%, 12%, and 16% solids content) and spray-dried. Encapsulation efficiency (85-98%) and radical scavenging activity (11-43%) varied proportionally with rice bran protein. Across increasing maltodextrin and rice bran protein content of the feed, carbohydrate content of the microcapsules varied proportionally (50-66%) but protein content was uniform (10-13%). Scanning electron microscopy, differential scanning calorimetry, and Fourier transform infrared spectroscopy data suggested successful encapsulation. Release profiles showed decreasing trend with increasing rice bran protein content; co-digestion with rice mitigated negative impacts of rice bran protein. Microcapsules with nutritive potential and health-promoting properties were developed as potential carotenoid delivery systems